Evaluation of Phenological Traits of Pear Varieties in Warm Temperate Region of Nepal - Padma Nath Atreya; Ramila Dhakal2; Jiban Shrestha (Agricultural Science, 2021)
Phenological study of a fruit tree is important for timely and proper orchard management. This study was carried out in orchard located at Warm Temperate Horticulture Centre (WTHC), Kathmandu, Nepal from January to August, 2020 with the objective to identify the different timing of phenological stages in 18 different varieties of pear. Data on days from swollen bud to bud burst, swollen bud to green cluster, swollen bud to white bud, swollen bud to bloom, swollen bud to petal fall, swollen bud to fruit set, fruit length, and fruit diameter were recorded. The phenological and fruit traits were found highly significant. The shortest flowering period (days from swollen bud to petal fall) was observed in varieties Sinko and Yakumo (13.33 days) and the longest period was found in Pharping local (Green) (35.00 days) followed by Pharping local (Brown) (34.00 days). The longest fruit (58.80 mm) was recorded in Anjou followed by Bartlett (52.90 mm) and Yakumo (49.80 mm). Similarly, the highest fruit diameter (57.60 mm) was recorded in Anjou followed by Yakumo (55.80 mm) and Atago (51.60 mm). On the basis of total variability, pear varieties were grouped into five distinct clusters. Cluster 2 showed that Anjou had the highest fruit length and fruit diameter. Cluster 5 illustrated that the longest flowering period was observed in the Pharping local (Green) followed by Pharping local (Brown). Based on phenological traits Sinko and Yakumo and based on fruits traits Anjou were found potential varieties for cultivation under warm temperate region of Nepal.